Semantic Similarity of LLM Explanations in Software Engineering Tasks - Andersson, Simon; Wang, Qianyuan (My University, 2026)
Large language models (LLMs) are increasingly used to generate natural-language explanations for software engineering (SE) tasks. However, it is still unclear how similar these explanations are across models when the task remains the same. We address this gap in two SE contexts: Python code comprehension and explaining requirements classifications. We use a controlled experimental design to compare GPT-4.1, Claude Sonnet 4, and Gemini 2.5 Flash under two prompt types: high level and detailed. In total, the experiment produces 240 explanations. We analyze these explanations from three complementary perspectives: embedding-based semantic similarity, manual reasoning pattern analysis using a predefined codebook, and perceived similarity and quality through a human survey and an LLM-as-a-judge evaluation. Our results show that explanations from different models are often close in meaning, but their similarity varies across model pairs, task types, and prompt conditions. The reasoning pattern analysis shows that models also differ in how they structure their explanations, and these differences depend on the task and prompt type. The quality evaluation of the selected explanation pairs shows that no model is consistently better than the others across all dimensions, and that human and LLM-as-a-judge judgments do not always agree. Therefore, evaluating LLM explanations in SE should combine semantic similarity measures, reasoning-structure analysis, and human or LLM-based quality judgments to support trustworthy use of these models in practice.
Keywords: Large language models, semantic similarity, explanation quality, explanation structure, LLM-as-a-judge